Desenvolvimento da floricultura tropical paraense: uma análise dos fatores locais de inovação - RIOS ARÉVALO, Michelly (Universidade Federal do Pará, 2019)
The aim of this study was the interaction of specific social communities in the tropical floriculture agglomeration of Pará. The focus was local producers in direct interaction with other agents of the sector in order to value local factors of innovation in tropical floriculture. Although tropical floriculture has a lower economic representation than temperate floriculture (found in other regions of Brazil) in the local scenario, in the short time it has been established, it has been considered by different public and private agents as an important economic activity for the state of Pará. However, there is evidence of agents who focus on social organizations, an alternative that reduces the “production costs” and the “transaction costs” of different activities that this sector demands. Among the communities studied are: the Benevides Florists Association(AFLORBEN), The Santo Antônio Agricultural Cooperative (COOPSANT), The Flower Producers Association of Santa Bárbara (TROPISAN), The Microproducers Association of Castanhal (BARREIRÃO), The Pará Association of Floriculture and Medicinal Plants (PARÁFLOR); and finally, the communities and/or agents that make up the commercial and institutional floricultural scene (The Social Network of the Local Flower Agglomeration of the Metropolitan Mesoregion of Belém). This last community was responsible for the implementation of the central object of the study, where the relevant organizational processes that value the factors of local innovation and their impact on the sustainable development of the sector were integrated. The methodology was based on the analysis of the social capital and of social networks, with an aim to recover the structure and functionality of the local society in relation to a dynamic and competitive market like floriculture itself. The results show that the organizational processes minimize the costs of transaction and help these social groups to remain on the market, and, therefore, value the tropical brand of flowers. Finally, it is suggested that more integrating and far-reaching processes be prioritized in order to strengthen this local activity even more.